Trabalho e saúde do professor nas pesquisas em educação - Oliveira, Michelle Ferreira de (2015)
This work is linked to the line of research Education, Work and social movements. The study aimed to analyze as they have been presented discussions about teachers' work and health in research conducted in the area of Education, presented and disclosed in the academic area productions (magazines classified by CAPES in A1 and published works in ANPEd), reported from 2004 to 2014. The research is characterized as bibliographic and was structured by a qualitative approach. The theoretical construction was based on reflections concerning the intensification of teachers' work and change processes in education policy that have occurred in recent decades in Brazil. We use authors as Assunção and Oliveira (2009), Fernandes (2010), Alves (2012), Enguita (1991), Brito (2005), among others, and we seek to understand the teachers' health and work relations considering the dynamicity of the human being. Thus, we appropriate of the authors discussion such as Assunção (2003), Esteve (2009), Alves (2010), Dejours (2004), Canguilhem (2012), Brito (2005), to understand how have being constituted the teachers' work and health discussions. The research here structured permeates the conceptual relations established in the scope of health, the teacher's work conception and the complex structure involving such relations, as well, aims to understand the individual as a dialogical living being that establishes relations from its fundamental activity, the work. There fore, we will use the ergonomics of activity as north to the productions and publications analysis, delimited for this bibliographic review, based on the understanding of human activity, appropriating up the concepts of prescribed work (task) and real work (performed activity). The data selection process it had as starting point the publications performed in all working groups of the ANPEd and magazines with qualis A1 classified by CAPES, in Portuguese language. Of this material, we established as cutting point studies that addressed discussions about work, health, intensification, disease, illness, teacher's malaise. From these characteristics we achieve to 23 productions that were related to teachers' work and health. The analysis of the information collected had as a starting point the questions: What is the central theme of the article? What concept of teachers' work? What the conception of health? Is there the work and health relation? The research enabled us to see the distinction between the different methodological approaches and organizations of the scope of health and as a result, in the set of analyzed studies, regarding the working conditions, there is consensus that the precarious and the very bad conditions experienced in schools infer in the teachers' health. It was evident that occurred theoretical advances with regard to the discussion of teachers' health and work among the researchers in the education field in Brazil, but we reiterate the need for studies that dialogue with statistical data from the real teacher's work analysis.